Effects of Gaze Cues on Distributive Behavior of the Ultimatum Game in Adults With Attention Deficit Hyperactivity Disorder. Issue 7 (13th July 2022) - Ikuse, Daisuke; Hayashi, Wakaho; Hanawa, Youichi; Nakamura, Dan; Arai, Gousuke; Saga, Nobuyuki; Iwanami, Akira
Abstract: Adults with attention deficit hyperactivity disorder (ADHD) have difficulty in social decision-making. The ultimatum game (UG) is a popular economic game used to evaluate social decision-making. This study aimed to examine the effects of schematically depicted eyes and ADHD symptoms on UG performance. Thirty adults with ADHD were recruited. The computer screen background was changed among the "eyespots, " "neutral, " and "flowers" conditions among 30 trials of UG. Through all trials, task performances were recorded, and then compared with 30 typical adults and 30 adults with autism spectrum disorder (ASD). The reaction time was not affected by the background in any group. Although typical adults distributed more money in the "eyespots" condition, a nonsignificant background effect was observed in adults with ADHD or ASD. These results may be associated with reduced attention to social cues in individuals with ADHD, and this ADHD characteristic might lead to difficulty in social decision-making.